Fine young people : a novel - Bruno, Anna, 1981- (Algonquin Books of Chapel Hill, 2025)
"Frankie is a good daughter, a loyal best friend, and a model student, coasting through her final semester at an elite Catholic prep school in a wealthy Pittsburgh enclave...When a classmate takes his life after posting a cryptic message about Woolf Whiting-a former student hockey player who died in a presumed suicide years earlier-Frankie and her best friend, Shiv, decide to investigate Woolf's death...Frankie speaks to his sister,...his former girlfriend, who Woolf's mother is convinced knows more about his death than she has revealed...As she does, she discovers much more than she expected about the history of her supposed elite education--and the truth about her own past"--